The Effect Of Service Quality And Price On Purchasing Decisions At Id Express Tamalate Makassar Branch - Emy Safitri; Aslinda; Maya Kasmita; Risma Niswaty; syarifuddin (Business Research and Administration Innovation, 2026)
This study aims to determine the effect of service quality and price on purchasing decisions at the ID Express Tamalate Makassar branch. Respondents in this study were users of ID Express services, Tamalate Makassar Branch, with a total sample of 100 respondents. The sampling technique used purposive sampling technique with data collection using a questionnaire. The data obtained were processed using SPSS 25, which consisted of validity and reliability tests on research instruments, classical assumption tests, multiple linear regression analysis and hypothesis testing. The results showed that the service quality variable had a positive and significant partial effect on purchasing decisions at ID Express, Tamalate Makassar Branch. The price variable has a partially positive and significant effect on purchasing decisions at ID Express, Tamalate Makassar Branch. The variables of service quality and price simultaneously have a positive and significant effect on purchasing decisions at ID Express, Tamalate Makassar Branch. This was proven based on the Correlation Test, T Test, F Test, and the Coefficient of Determination Test on the data obtained.